Principales factores que influyen en la producción del cultivo de tabaco (Nicotiana tabacum L) en la Provincia de los Ríos - ARTEAGA LEDESMA, MICHAEL JOSEPH (2023)
The purpose of this document was to identify the main factors that influence tobacco (Nicotiana tabacum L) crop production in Los Rios Province. It was developed as a non-experimental component of bibliographic character, through the technique of analysis, synthesis and summary of the information obtained. Tobacco crop is one of the most susceptible species to the influence of different production factors that integrate the environment where they develop. The edaphoclimatic factors involved in tobacco crop production are the following: climate, heliophany, crop water requirement, temperature, humidity and soil. The ideal temperature for an adequate development and growth of the tobacco crop is between 18-28ºC. Tobacco is extremely sensitive to the need or excess of moisture; a high degree of moisture in the soil produces negative effects on crop development. In the tobacco crop, high light intensity decreases the size of the leaves and increases their thickness. The establishment distance for about 30,000 plants/ha is 1.05 m between columns and 30 cm between plants, being an important factor that depends on the variety to be planted. The best seedbeds for tobacco are those that meet the following qualities: loose soil, with large surface and drainage; being the seedbeds the most important phase to achieve an excellent crop. The genetic materials established in Ecuador are: oriental, black and burley. Within the management of the main agricultural tasks in the tobacco crop are the following activities: seedbed, transplanting, soil preparation, planting, planting distance, crop nutrition, irrigation, weed control, leaf suppression, trimming and weeding, insect pest and disease management, harvesting, lifting, binding or stringing, curing and harvesting.